2011
DOI: 10.1063/1.3562328
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of defect-induced ferromagnetism and its “switch” action in pristine bulk TiO2

Abstract: In this work, we demonstrate that room temperature ferromagnetism can be induced in pristine anatase TiO2 paramagnetic bulk powder through extended hydrogenation. Defect complexes, Ti3+–VO (Ti3+ ions accompanied by oxygen vacancies) are clearly identified in hydrogenated TiO2 by combining x-ray diffraction and photoemission spectroscopy. The observed ferromagnetic ordering is reversible that can be switched between “on” and “off” by inducing or removing, respectively, these defect complex. We convincingly eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 20 publications
3
29
2
Order By: Relevance
“…A lot of further researches concerning their ferromagnetism mechanisms and the impact factors have been carried out, and various debates are never scarce. In recent research works, additional defects such as oxygen vacancies or H interstitials were proved to play an important role in establishing or enhancing the magnetic couplings both in oxides compound [13][14][15] and doping compounds [16][17][18]. Many types of oxide semiconductors such as HfO 2 , CeO 2 , CaO, etc.…”
Section: Introductionmentioning
confidence: 98%
“…A lot of further researches concerning their ferromagnetism mechanisms and the impact factors have been carried out, and various debates are never scarce. In recent research works, additional defects such as oxygen vacancies or H interstitials were proved to play an important role in establishing or enhancing the magnetic couplings both in oxides compound [13][14][15] and doping compounds [16][17][18]. Many types of oxide semiconductors such as HfO 2 , CeO 2 , CaO, etc.…”
Section: Introductionmentioning
confidence: 98%
“…[2][3][4][5][6][7]9 On the other hand, first-principles calculations indicate that local magnetic moments are due to cation vacancies in CaO, 10 HfO 2 , 11 ZnO, 12 SnO 2 , 13 and TiO 2 14 while V O cannot induce local moments. Both experimental evidences [2][3][4][5][6][7][8][9] and theoretical studies [10][11][12][13][14] revealed that the ferromagnetism is induced by intrinsic defects in undoped oxides. However, whether cation vacancy or anion vacancy defect contributes to the RT ferromagnetism is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…So far, "d 0 " ferromagnetism has been observed in undoped TiO 2 , [2][3][4][5][6] In 2 O 3 , 2,7 ZnO, 7,8 and SnO 2 7,9 films, nanoparticle and nanoribbons. Most experimental evidences indicate that the RT ferromagnetism in these undoped oxides is induced by V O .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Singhal et al also reported the RTFM in pristine anatase TiO 2 paramagnetic bulk through extended hydrogenation. 25 The defect complexes of Ti 3+ -V O are clearly identified in hydrogenated TiO 2 and they elucidate that the factors of Ti 3d-O 2p hybridization, F + centers, and oxygen vacancy assisted fragmentation of grains, compositely contribute to the ferromagnetic ordering. The F-center exchange mechanism has been used to explain observed FM, which also may explain the observed FM in our case.…”
mentioning
confidence: 99%